Photonic Crystal Slab Add-Drop Filter - Mohammad Reza Rakhshani; Mohammad Ali Mansouri-Birjandi (International Journal of Advances in Applied Sciences, 2013)
A new type of optical add drop filter (ADF) based on slab photonic crystals resonant cavities is proposed. ADF operation is based on coupling between the photonic crystal waveguides. Using the finite difference time domain (FDTD) method and plane wave expansion (PWE) method, the ADF characteristics and band structure of the filter, respectively are obtained. The proposed structure is optimized to work as an ADF. Dropping efficiency at 1560nm and quality factor (Q) of our proposed structure are 90% and 195, respectively. The quantities of quality factor and transmission efficiency are suitable for optical applications. This structure is highly attractive for photonic integrated circuits (PICs).